Assessing learning in a sociology department: what do students say that they learn?. Issue 3 (2nd April 2016) - Bandini, Julia; Shostak, Sara; Cunningham, David; Cadge, Wendy
Abstract : Assessment plays a central role in evaluating and strengthening student learning in higher education, and sociology departments, in particular, have increasingly become interested in engaging in assessment activities to better understand students' learning. This qualitative study builds on previous research on assessment by asking what students in one American university department see themselves learning in the sociology major. Rather than asking students to reflect on what we think they are learning, we asked open-ended questions about skills, topics and modes of education they considered most significant to their learning. The 25 sociology majors in our study included second-year students, graduating fourth-year students and alumni who had graduated five years prior, enabling us to compare what students have learned or are learning across cohorts. Our findings demonstrate that students emphasise a common collection of skills, topics and – especially – modes of learning in the major, despite their various course selections and interests within the discipline, and also that majors' orientations to sociology vary as they move through, and beyond, the undergraduate curriculum.